Revitalisasi Kepala Madrasah Dalam Meningkatkan Kualitas Madrasah di Madrasah Aliyah Ma’arif Al-Asy’ari - Lailatul Maulydyah, Nurul; Nabil Hisyam, Muhammad; Alin Nurdiani, Asmita; Ana Oktasari, Dwi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
In educational institutions, of course, there must be good leaders in implementing and managing the educational environment effectively so that it can produce significant citizens and learning facilities, but in this study there is a problem, namely the lack of teacher competence in the use of technology in the teaching and learning process where the head of the madrasah still cannot provide access to training and seminars in developing teacher skills in the use of current technology. So this study examines the impact of the leadership process of the head of the madrasah to support the value of the madrasah at MA Ma'arif Al-Asy'ari, Pasuruan Regency, Gondangwetan District. Qualitative techniques are used in this study to present the empirical state of the progress of the madrasah and its implications for the value of education. Observations, interviews, and documentation based on school activity data are used as data collection techniques. Analysis of research results requires premises and formulates action planning based on research. The results of the study showed that the head of MA Ma'arif Al-Asy'ari, Pasuruan Regency, Gondangwetan District, still could not provide access to competency development in the use of technology in learning, but the head of the madin had conveyed motivation to teachers to utilize the use of technology, and could unite a sense of harmony between teachers and madrasah staff, as well as to be able to develop the quality of the madrasah to the community so that it becomes a good attraction. Therefore, this study discusses the revitalization of the head of the madin which has implications for the quality of the madrasah